Plan de negocio para la instalación de una planta procesadora y comercializadora de longanizas en la parroquia San Camilo, cantón Quevedo, año 2014 - Briones Mera, Leonor Moralina (2015)
The present study was conducted to establish the technical, economic and financial feasibility for the installation of a processing plant for sausages, through a business plan, located in the San Camilo parish Quevedo Canton; for this purpose methods, techniques and research instruments was applied to a rapprochement with the current situation under study. The situational analysis found that 63% of the target population consumes sausage; and it was established that only 20% of the sausage that is sold in the local market is well-known brands. The percentage of acceptance by end users of sausages was in favor of the installation of the processing plant sausages; and 50% of commercial match for the project. Technical, economic and financial study show an IRR of 97%, higher than the minimum acceptable MEJOR PERFORMANCES rate, the NPV of $ 88,056.92, positive or greater than zero; cost and profit of $ 1.10. Therefore the project for intalacion sausage processing plant as feasible and profitable qualifies.